Perpetuating Imogene King’s Legacy in Nursing Practice - Teodora Duarte-Quilao (Nursing Science Quarterly, 2026)
This article is an introduction to a book review of Imogene King’s conceptual framework and theory of goal attainment , authored by Newman et al. (2025). This book revisits King’s Conceptual systems and the theory of goal attainment across worldwide research, and articulates King’s foundational philosophical virtues and faith tradition, implicitly linking her spirituality to Roman Catholic Christianity.